The impossible equation 2

Algebra Level 2

If a , b a,b and c c are distinct numbers where a b c 0 abc\ne0 , solve for the value of m m in 2 a b + c = 2 b a + c = 2 c a + b = m \dfrac{2a}{b+c}=\dfrac{2b}{a+c}=\dfrac{2c}{a+b}=m


The answer is -2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Jovan Boh Jo En
Feb 23, 2018

2 a b + c = 2 b a + c \dfrac{2a}{b+c}=\dfrac{2b}{a+c} 2 a ( a + c ) = 2 b ( b + c ) 2a\left(a+c\right)=2b\left(b+c\right) 2 a 2 + 2 a c = 2 b 2 + 2 b c 2a^2+2ac=2b^2+2bc a 2 + a c = b 2 + b c a^2+ac=b^2+bc a c b c = b 2 a 2 ac-bc=b^2-a^2 c ( a b ) = ( b + a ) ( b a ) c\left(a-b\right)=\left(b+a\right)\left(b-a\right) c = ( b + a ) ( b a ) ( a b ) c=\dfrac{\left(b+a\right)\left(b-a\right)}{\left(a-b\right)} = ( b + a ) ( b a ) ( a b ) =\dfrac{-\left(b+a\right)\left(b-a\right)}{-\left(a-b\right)} = ( b + a ) ( b a ) ( b a ) =\dfrac{-\left(b+a\right)\left(b-a\right)}{\left(b-a\right)} c = ( b + a ) c=-\left(b+a\right) 2 c a + b = m \dfrac{2c}{a+b}=m m = 2 × ( b + a ) a + b m=\dfrac{2\times -\left(b+a\right)}{a+b} = 2 × 1 =2\times-1 = 2 =\boxed{-2}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...